Malaria mitochondrial diagnosis: challenges and pitfalls - Costa, Gabriel Luíz; Alvarenga, Denise Anete Madureira de; Assis, Gabriela Maíra Pereira de; Aguiar, Anna Caroline Campos; Louzada, Jaime; Pereira, Dhélio Batista; Pina-Costa, Anielle de; Hirano, Zelinda Maria Braga; Moreira, Sílvia Bahadian; Pissinatti, Alcides; Brasil, Patrícia; Daniel-Ribeiro, Cláudio Tadeu; et al. (Frontiers in Tropical Diseases, 2023)
Background High-copy genomic sequences could be used as PCR targets for the detection of Plasmodium infections, providing increased sensitivity over single- or low-copy genes. Mitochondrial genomes of malaria parasites are present in multiple copies in a single mitochondrion, and each parasite has many mitochondria. Here, we describe the development of seven species-specific qPCR assays for the diagnosis of Plasmodium vivax and Plasmodium falciparum, targeting coding and non-coding mitochondrial genomic regions. Methods The optimization of the qPCR protocols involved a gradient of annealing temperatures and concentrations of primers and probes, as well as the inclusion of PCR additives/enhancers [e.g., dimethyl sulfoxide (DMSO), glycerol, bovine serum albumin (BSA)] to improve the specificity of qPCR amplification. Results Non-specific amplification of other Plasmodium species and of human targets was observed in different levels for all assays. Regardless of the late Cq values for most non-specific amplifications, the application of a cutoff value did not completely exclude false-positive amplification, compromising the specificity and also the sensitivity of the assays. Conclusions Therefore, although mitochondrial targets have higher sensitivity, they frequently lose specificity due to their high levels of sequence conservation. A screening to evaluate the cross-reaction between Plasmodium species and the non-specific amplification of human malaria-free samples must be performed for Plasmodium mitochondrial assays.